Cyprus : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2011)
The Selected Issues Paper focuses on Cyprus' banking sector vulnerabilities and its pension system. The most salient risks for the banking sector come from commercial banks domiciled in Cyprus. These banks have the strongest links with the local economy and are likely to experience further deterioration of their loan portfolios in both Greece and Cyprus. The paper reveals that, in 2011, Cypriot banks face capital needs estimated at Euro 3.6 billion on a preliminary basis.